Strategi Pembelajaran PAUD Berbasis Kecerdasan Majemuk di KB-RA Al-Azhar Gresik - Muhammad Mahfud (AT-THUFULY : Jurnal Pendidikan Islam Anak Usia Dini, 2020)
Early childhood is a time of golden age, because at this time the child's intelligence develops quickly and rapidly. Intelligence of the child is extremely diverse, even one psychologist Gardner m found very diverse kinds of human intelligence is not just intelligence alone. Opinion was then known as the concept of multiple intelligences. ECD Al-Azhar is an early childhood education institutions that in learning to use the concept of multiple intelligences development of students. Therefore, this study aims to find out more about the various strategies that can be employed in the multiple intelligences-based early childhood learning, implementation efforts, both factors that support and subservience, as well as the efforts undertaken ECD Al-Azhar in tackling the various obstacles faced.This research is a research study kualitatif with a case study approach. The population in this study are all elements involved in the organization of early childhood education. The results showed that early childhood learning strategy based on multiple intelligences performed ECD Al-Azhar is by first dissecting the curriculum. Then the results are carried out in accordance with the learning SKS, SKM, and SKH that have been prepared. Its implementation is done with 3M maximization maximization method, style, and instructional media. The factors that contributed to the passage of early childhood learning program is competency-based intelligences principal, teacher competence, and density. While the factors that impede the form of the ever-changing curriculum content, there are some teachers who are less creative and a lack of infrastructure and facilities required from year to year. To overcome this the foundation and the principal do a higher priority to the needs of teachers and schools.